2019
DOI: 10.18203/2320-6012.ijrms20193931
|View full text |Cite
|
Sign up to set email alerts
|

Comparison between the results of proximal femur nail anti-rotation and cemented bipolar hemiarthroplasty in treatment of intertrochanteric fractures in Sanglah Hospital in 2016

Abstract: Background: Hemiarthroplasty is now being considered as a primary treatment for comminuted unstable type of IT fracture in elderly on the grounds that it allows early mobilization and full weight bearing. Recently popular modality is fourth generation of intramedullary nails like the Proximal Femoral Nails. The goal of treatment is restoring mobility safely and efficiently, while minimizing the risk of medical complications and technical failure.Methods: A Forty patients, having Intertrochanteric fractures tre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
1
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 3 publications
0
1
0
Order By: Relevance
“…Prasad et al [2] reported similar results with ages of 67 years and 57 years in the hemiarthroplasty and osteosynthesis groups, respectively. Other studies by Dusak et al [11] and Dash [12] also reported similar results. The distribution of the cases among gender was comparable in all the above-mentioned studies with predominance seen in the female population.…”
Section: Discussionsupporting
confidence: 76%
See 1 more Smart Citation
“…Prasad et al [2] reported similar results with ages of 67 years and 57 years in the hemiarthroplasty and osteosynthesis groups, respectively. Other studies by Dusak et al [11] and Dash [12] also reported similar results. The distribution of the cases among gender was comparable in all the above-mentioned studies with predominance seen in the female population.…”
Section: Discussionsupporting
confidence: 76%
“…There was a significant difference between the two (p < 0.001) (Table 3). Dusak et al [11] and Patil [13] reported similar results. The Harris Hip Score was calculated at the second, fourth, and sixth-month follow-ups and was found to be significant when compared between the two groups.…”
Section: Discussionsupporting
confidence: 52%
“…6 However, research by Dusak et al of patients with intertrochanter femur fractures showed no significant difference from functional results measured by the Harris Hip Score, between the PFNA group (72) with bipolar hemiarthroplasty (69). 7 The objective of this study was to compare the mortality rates and LoS after bipolar hemiarthroplasty and PFNA fixation for intertrochanteric fracture, so that it could became a helpful basis for preoperative decision making in choosing between those two widely used treatments.…”
Section: Introductionmentioning
confidence: 99%